Home Country Institutions and the Internationalization-Performance Relationship - Marano, Valentina; Arregle, Jean-Luc; Hitt, Michael A.; Spadafora, Ettore; van Essen, Marc (Journal of Management, 2016)
We propose that the mixed findings of research on the internationalization-performance (I-P) relationship reflect its failure to adequately consider the moderating role of firms’ home country formal and informal institutions. This general hypothesis is supported in a meta-analysis of the firm-, industry-, home country–, and host country–level factors driving the I-P relationship across 32 countries between 1972 and 2012 from 359 primary studies—the largest sample of primary studies of any meta-analysis on this topic to date. We make three main contributions to the I-P and global strategy literatures. First, we develop a novel integration of the theoretical logics from the I-P research and the institution-based view of strategy to explain how embeddedness in home country institutions affects the strength of the I-P relationship. Second, we show the importance of including both formal and informal institutions in analyses of firms’ institutional embeddedness, thereby extending our knowledge of the effects of institutional complexity. Our third contribution is methodological and reflects our use of advanced meta-analytical techniques based on both product-moment and partial correlations as effect sizes, which allow us to address unresolved debates about the sign and shape of the I-P relationship. Our results show that the I-P relationship is positive, although the overall effect is small and varies greatly across firms’ home countries. We conclude by discussing the findings’ relevance and promising future research avenues, including novel research questions, multilevel theoretical and empirical frameworks, and improvements in methodological rigor.